Monitoring and modeling of field infestations and damage by the maize ear borer Mussidia nigrivenella Ragonot (Lepidoptera: Pyralidae) in Benin, West Africa - Sétamou, M.; Schulthess, F.; Poehling, H.; Borgemeister, C. (Oxford University Press, 2000)
In many countries in West Africa, the pyralid ear borer Mussidia nigrivenella Ragonot occasionally causes severe damage to pre- and postharvest maize. Between 1992 and 1995, the distribution of and damage caused by M. nigrivenella were studied in Benin using survey data and an on-station field experiment. The borer was distributed across the whole country, and at maturity an average 25% of the ears sampled in maize fields were infested. Damage levels varied with agro-ecological zones and were highest in the Guinea Savannas. However, borer-related yield losses were comparatively low. Three applications of cypermethrin over the growing season did not provide sufficient control in the on-station field experiment. A model was developed to estimate maize losses caused by M. nigrivenella, using the percentage of infested ears, which explained 93% of the variance. Extrapolation of field data indicated a 25% yield loss once a 100% infestation of maize ears was reached. For surveys in maize fields the model is a valid tool for a rapid assessment of crop losses caused by M. nigrivenella.